2019
DOI: 10.1111/1365-2664.13460
|View full text |Cite
|
Sign up to set email alerts
|

Tree performance in a biodiversity enrichment experiment in an oil palm landscape

Abstract: Large‐scale conversion of tropical forests into oil palm monocultures has led to dramatic losses of biodiversity and ecosystem functions. While ecological restoration is urgently needed in many oil palm landscapes, there is a lack of scientific knowledge of sustainable management strategies. We established experimental tree islands of varying sizes (25 m2 to 1,600 m2) and diversity levels (1, 2, 3 and 6 species) in an oil palm plantation in Sumatra, Indonesia. Six native multi‐purpose tree species including Ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 64 publications
0
32
0
Order By: Relevance
“…The relative importance of tree richness, tree species identity, and plot size was quantified using a linear model for random partition design [46] that was adapted to the design of EFForTS-BEE [42,44]. This design includes terms for tree species richness treated as a continuous variable (i.e., 0, 1, 2, 3, or 6), a numeric matrix indicating the presence or absence of each tree species, the number of planted tree species as a discrete variable ("nonlinear species richness"), and plot size.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The relative importance of tree richness, tree species identity, and plot size was quantified using a linear model for random partition design [46] that was adapted to the design of EFForTS-BEE [42,44]. This design includes terms for tree species richness treated as a continuous variable (i.e., 0, 1, 2, 3, or 6), a numeric matrix indicating the presence or absence of each tree species, the number of planted tree species as a discrete variable ("nonlinear species richness"), and plot size.…”
Section: Discussionmentioning
confidence: 99%
“…This study was conducted in the framework of the biodiversity enrichment experiment EFForTS-BEE of the Collaborative Research Center 990 [42,44]. The research site is located in a commercial oil palm plantation (PT Humusindo Makmur Sejati, 01.95 south (S) and 103.25 east (E), 47 ± 11 m above sea level (a.s.l.))…”
Section: Research Site and Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental and observational research alike has shown that biodiversity often promotes ecosystem functions such as productivity (Tilman et al 2014). In forests, this trend has been shown in both experimental (Potvin & Gotelli 2008;Tobner et al 2016;Grossman et al 2017;Williams et al 2017;Huang et al 2018;Zemp et al 2019) and observational (Gamfeldt et al 2013;Liang et al 2016;Oehri et al 2017) data, across temperate (Tobner et al 2016;Grossman et al 2017;Williams et al 2017), subtropical (Huang et al 2018), and tropical (Potvin & Gotelli 2008;Zemp et al 2019) biomes. These positive relationships are robust to variation in climate, successional stage, and other factors (reviewed in Grossman et al 2018;Ammer 2018).…”
Section: Introductionmentioning
confidence: 95%
“…The majority of studies have largely focused on comparing oil palm with natural habitats, with fewer studies that have specifically tested the effects of plantation management strategies on environmental conditions, biodiversity, or ecosystem functions (Savilaakso et al, ). Although recent research efforts have given more attention to the effects of possible management strategies (e.g., Ashraf et al, ; Azhar et al, ; Darras et al, ; Ghazali et al, ; Teuscher et al, ; Zemp et al, in a smallholder context), given the huge global coverage of the crop, there is an urgent need to further investigate management techniques that can support biodiversity within plantations without reducing yield. This is particularly the case for taxa that contribute toward important ecosystem services associated with crop production, therefore, potentially benefitting both biodiversity and yield.…”
Section: Introductionmentioning
confidence: 99%